Manajemen Public Relations Dalam Pengelolaan Event Jambore Nasional Bank Sampah - Dewanggi I.B, Anggun Putri; Mekarsari, Anggun (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2024)
The Ministry of Environment and Forestry (KLHK) is a government agency that handles environmental problems in Indonesia, including waste. The large amount of waste in Indonesia shows that it still needs serious handling. The Budi Luhur Waste Bank, which is one of the largest waste banks in Indonesia, together with the Ministry of Environment and Forestry, is holding the National Waste Bank Jamboree. This research aims to describe and analyze the implementation of the National Waste Bank Jamboree in supporting the resolution of the national waste problem. This research uses the concept of 4 stages of Cutlip and Broom PR management. This research is post positivist, qualitative research, with descriptive analysis methods. The research subject is the National Waste Bank Jamboree committee. The research object is the organization of the National Waste Bank Jamboree. Research time July 2023 – August 2023. Research location: Budi Luhur University campus, as the location for the National Waste Bank Jamboree. Data validity uses source triangulation. Data analysis is carried out by sorting, categorizing, describing and analyzing data. The results of this research are searching for data and facts to define the problem, carrying out planning and programming by determining the venue, organizing team and series of events, taking action and communicating through the organization's internal and external media channels, social media platforms, press conferences and press releases, and evaluate the program through the results of event reports and monitoring media publications.